Cultural Adaptation of a Community-Based Hearing Health Intervention for Korean American Older Adults with Hearing Loss - Choi, Janet S. (J Cross Cult Gerontol, 2019)
Although hearing loss is known to be associated with many adverse health outcomes in older adults, current hearing healthcare remains expensive and inaccessible to most ethnic minorities in the US. We aim to adapt an affordable, community-based hearing intervention to older Korean Americans (KAs), describe the cultural adaption process, and report pilot trial outcomes. We undertook the first four stages of Barrera & Castro’s cultural adaptation framework: information gathering, preliminary adaptation design, adaptation test, and adaptation refinement in 15 older KAs with hearing loss and 15 of their communication partners. We developed a culturally adapted intervention consisting of provision of an affordable listening device and aural rehabilitative training. Six weeks post-intervention, participants’ mean hearing handicap score (range: 0-40) reduced from 15.7 to 6.4. Communication partners demonstrated improved social-emotional function. Post-intervention focus group revealed increased hearing benefit, confidence in hearing health navigation, and awareness in hearing health among study participants. The adapted intervention was well-accepted and feasible among older KAs. This study is the first to report the cultural adaptation process of a hearing care model into older KAs and its methodology may be applied to other minority groups.